Monitorando informações nas mídias sociais online - Tiago Rodrigues de Magalhaes (2012)
Online Social Media services (blogs, social networks) are important communication tools in the modern world. Tradicionally, people find information in the web by browsing or searching. With the recent success of Online Social Media, people started to receive information from conversations with their friends. A huge and diverse amountof information is generated everyday by millions of people all over the world. As an example, on Twitter users share and forward information about events in real-time; on Facebook, users get to know about what their friends did on the last weekend; and on Fourquare users discover where their friends visited recently. The huge volume of data, the diversity of information, the dynamic of the systems, and the need for real-time information leads to big challenges while processing and analyzing the user generated data from Online Social Media services. However, a better understanding about the information diffusion process in Online Social Media services is necessary, not only for users, but also for companies and researchers. Advertising, better content organization, and creation of new tools are examples of possible benefits from a betterunderstanding of the problem. In this work we propose MIOSphere, a system to monitor, in real-time, the diffusion of information through popular Online Social Media services. Furthermore, a wide characterization of the diffusion of URLs on Twitter was done, analyzing not only the internal diffusion, but also how URLs generated inexternal services (YouTube videos, for example) diffuses on Twitter.